2003
DOI: 10.1002/anie.200352382
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylsilyl Pentafluorophenylbis(trifluoromethanesulfonyl)methide as a Super Lewis Acid Catalyst for the Condensation of Trimethylhydroquinone with Isophytol

Abstract: Acid and vitamin E: Trimethylsilyl super Lewis acids, such as [C6F5C(Tf)2]− Me3Si+ and Tf3CSiMe3, are extremely active and highly effective catalysts for the regioselective condensation of trimethylhydroquinone with isophthyol to afford (±)‐α‐tocopherol (vitamin E; see scheme, Tf=CF3SO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 22 publications
0
48
1
1
Order By: Relevance
“…11). From a chemical and biological point of view, -tocopherol is the most active form of Vitamin E group [36][37]. This reaction is not only a good test for the acid site types but is also interesting from an economical point of view, due to the high market demand for this compound and the various environmental problems that industry faces with the currently used homogeneous catalysts.…”
Section: Hydroxylated Metal Fluoridesmentioning
confidence: 99%
“…11). From a chemical and biological point of view, -tocopherol is the most active form of Vitamin E group [36][37]. This reaction is not only a good test for the acid site types but is also interesting from an economical point of view, due to the high market demand for this compound and the various environmental problems that industry faces with the currently used homogeneous catalysts.…”
Section: Hydroxylated Metal Fluoridesmentioning
confidence: 99%
“…Since the condensation of 2 and 3 to 1 possibly proceeds through Friedel-Crafts alkylation-cyclization [4,7,8,10a,12] or an orthoClaisen rearrangement of an intermediary allyl ester, [13,14] the use of non-polar reaction media would suppress the formation of the secondary cation from 3, to minimize the formation of the undesired five-membered by-products 4. In fact, it has been reported that the selectivity of 1 attained in a non-polar solvent, heptane, is markedly improved, [2] while the chemical yield of 1 is maximized in polar aprotic solvents. [4,10a] Thus, the reaction chemistry of the condensation to 1 in…”
mentioning
confidence: 99%
“…We first measured the solubility of the fluorinated catalyst 5a as well as the substrates 2 and 3 in scCO 2 . The catalyst 5a proved to be fairly soluble in scCO 2 ; the solubility was estimated to be 5.0 mmol/L by 19 F NMR spectroscopy [17] under supercritical conditions, 40 8C and 8.5 MPa.…”
mentioning
confidence: 99%
See 2 more Smart Citations